Trolls [videorecording (Blu-Ray)] - Aibel, Jonathan, 1969-; Berger, Glenn (Universal Pictures Home Entertainment, 2018)
When their village is invaded by the grumpy Bergens, two mismatched friends must work together in perfect harmony to save the day. Featuring hit songs performed by Justin Timberlake, Anna Kendrick, and more.